Advances in the Relationship Between Pyroptosis and Diabetic Neuropathy - Xu, Jingyu; Cai, Shufang; Zhao, Jiaxin; Xu, Ke; Ji, Hao; Wu, Chengbiao; Xiao, Jian; Wu, Yanqing (Frontiers in Cell and Developmental Biology, 2021)
Pyroptosis is a novel programmed cell death process that promotes the release of interleukin-1β (IL-1β) and interleukin-18 (IL-18) by activating inflammasomes and gasdermin D (GSDMD), leading to cell swelling and rupture. Pyroptosis is involved in the regulation of the occurrence and development of cardiovascular and cerebrovascular diseases, tumors and nerve injury. Diabetes is a metabolic disorder characterized by long-term hyperglycemia, insulin resistance and chronic inflammation. The people have paid more and more attention to the relationship between pyroptosis, diabetes and its complications, especially its important regulatory significance in diabetic neurological diseases, such as diabetic encephalopathy (DE) and diabetic peripheral neuropathy (DPN). This article will give an in-depth overview of the relationship between pyroptosis, diabetes, and its related neuropathy, and discuss the regulatory pathway and significance of pyroptosis in diabetes-associated neuropathy.